A new genus and two new species of feather lice (Phthiraptera: Ischnocera: Philopteridae) from New Zealand endemic passerines (Aves: Passeriformes) - Valim, Michel P.; Palma, Ricardo L. (Zootaxa, 2015)
The first descriptions of New Zealand endemic feather lice belonging to the Brueelia-complex (Phthiraptera: Ischnocera: Philopteridae) are given. The new genus Melibrueelia and new species M. novaeseelandiae are described, illustrated and compared with morphologically close taxa within the complex. The type host of M. novaeseelandiae is the tui, Prosthemadera novaeseelandiae (Gmelin, 1788), and an additional host is the bellbird, Anthornis melanura (Sparrman, 1786) (Passeriformes: Meliphagidae), both endemic to New Zealand. Also, the new species Brueelia callaeincola is described and illustrated from four endemic bird species belonging to two endemic genera and an endemic family: Philesturnus carunculatus (Gmelin, 1789) (the type host), Ph. rufusater (Lesson, 1828), Callaeas cinerea (Gmelin, 1788) and C. wilsoni (Bonaparte, 1851) (Passeriformes: Callaeidae). Brief discussions on possible evolutionary histories of the new taxa are included.